Face image analysis via Transformers: Algorithms and applications for face beauty assessment - Boukhari, Djamel Eddine (جامعة الواديUniversité d'eloud, 2024)
لطالما كانت النظرة إلى الجمال موضوعاً محورياً في المجتمع البشري، حيث تتشكل هذه النظرة من خلال التأثيرات الاجتماعية والاقتصادية والثقافية والتاريخية. على الرغم من تطور الآراء حول جمال الوجه في جميع أنحاء العالم، إلا أن فهم العوامل الكامنة وراء جاذبية الوجه لا يزال مجالاً رئيسياً للاهتمام في تخصصات مثل علم النفس وعلم الحاسوب وعلم الأحياء التطوري. ومع التطورات في مجال الرؤية الحاسوبية والتعلم العميق، برز التنبؤ بجمال الوجه (FBP) كمجال متطور يتيح القياس الموضوعي لجمال الوجه والعوامل الكامنة وراءه. تقترح هذه الأطروحة أربعة مناهج جديدة للتنبؤ بجمال الوجه باستخدام التعلم العميق. تستفيد مقاربتان من الشبكات العصبية التلافيفية (CNNs) المدمجة مع التعلم التجميعي، وتجمع بين تنبؤات من نماذج متعددة لتحسين الدقة. أما الطريقتان المتبقيتان فتستفيدان من قوة محولات الرؤية، باستخدام آليات الانتباه لالتقاط العلاقات المعقدة في ملامح الوجه. تعمل هذه الأساليب معًا على تحسين تمثيل الملامح وتحليلها من أجل تقييم قوي وموثوق لجمال الوجه. تُظهر التجارب التي أُجريت على مجموعة البيانات القياسية SCUT-FBP5500 فعالية أساليبنا. لقد حققنا أداءً فائقًا من خلال مقارنة نماذج التعلم العميق المختلفة، بما في ذلك AlexNet وResNet-18 وResNeXt-50. تُسفر النماذج المقترحة عن تنبؤات تتوافق بشكل وثيق مع التقييمات البشرية، متجاوزةً بذلك الأساليب التقليدية في الدقة والاتساق. تؤكد هذه الأطروحة على التأثير التحويلي The perception of beauty has long been a central topic in human society, shaped by socioeconomic, cultural, and historical influences. Despite the evolving opinions on facial beauty worldwide, understanding the factors behind facial attractiveness remains a key area of interest across disciplines such as psychology, computer science, and evolutionary biology. With advancements in computer vision and deep learning, facial beauty prediction (FBP) has emerged as a cutting-edge field, enabling objective quantification of facial beauty and its underlying factors. This thesis proposes four novel approaches to facial beauty prediction using deep learning. Two approaches leverage convolutional neural networks (CNNs) integrated with ensemble learning, combining predictions from multiple models to improve accuracy. The remaining two approaches harness the power of Vision Transformers, utilizing attention mechanisms to capture intricate relationships within facial features. Together, these methods enhance feature representation and analysis for robust and reliable facial beauty assessment. Experiments conducted on the SCUT-FBP5500 benchmark dataset demonstrate the effectiveness of our approaches. We achieve superior performance by comparing various deep learning models, including AlexNet, ResNet-18, and ResNeXt-50. The proposed models yield predictions that closely align with human evaluations, surpassing conventional methods in accuracy and consistency. This thesis underscores the transformative impact of deep learning in facial beauty prediction, offering precise, unbiased, and automated evaluations of facial attractiveness.
أطروحة
Keywords: التنبؤ بجمال الوجه; الشبكات العصبية التلافيفية; محولات الرؤية; التعلم التجميعي; التجميعي، تقييم الأداء